Dietary purslane modulates gut microbiota and fecal metabolites in aging rats - Deng, Jingwen; Wang, Xia; Yan, Can; Huang, Zicheng; Luo, Hui; Dai, Caihua; Huang, Xiaoliu; Huang, Yushan; Fu, Qiang (Frontiers in Microbiology, 2025)
IntroductionPortulaca oleracea L. (purslane) is a highly nutritious and edible wild vegetable beneficial to human health. However, its impacts on the structure of gut microbiota and fecal metabolites in aging individuals remain unclear. This study aims to clarify its potential mechanisms in aging-related gut health.MethodsNaturally aged rats (18 months) were divided into two groups. One group was fed a maintenance chow, and the other was fed a mixture with 3.5% purslane for 15 weeks. Hematoxylin-eosin staining, gas chromatography-mass spectrometry, and 16S rDNA high-throughput sequencing were employed to explore the effects of purslane on the intestinal health of these rats.ResultsThe fecal concentrations of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, and total short-chain fatty acids (SCFAs) were significantly increased in aging rats fed the purslane supplement. Purslane significantly reduced the relative abundance levels of Firmicutes and Fusobacteria, as well as the ratio of Firmicutes to Bacteroidetes. KEGG pathway analysis annotated 109 differential metabolites, which mainly affected metabolic pathways such as linoleic acid metabolism, arachidonic acid metabolism, primary bile acid biosynthesis, steroid biosynthesis, and steroid hormone biosynthesis. There was a strong correlation between Paracbacteroides, the Prevotella NK3B31_group, the Rikenella_RC9_gut_group, and SCFA levels. Aging rats consuming purslane had a more complete and healthy gut morphology than the control group.DiscussionThese results suggested that the maintenance of intestinal health by purslane in aging rats might be associated with the targeted regulation of gut microbiota and fecal metabolites.